The role of organizational flexibility in applying electronic human resource management practices - Mahmood , Nechirvan; Dawda, Range; Muhammad, Jalal (Humanities Journal of University of Zakho, 2022)
The research aims to verify the role of organizational flexibility as an independent variable represented in dimensions: strategic flexibility, structural flexibility, and operational flexibility in the application of electronic human resources management practices as an independent variable represented by its dimensions: electronic polarization and selection, electronic training and development, electronic performance evaluation, electronic compensation. The main and sub-hypotheses related to correlation and influence relations between research variables were tested in a number of private universities in the Kurdistan Region - Iraq. The sample consisted of 106 heads of departments and officials of administrative units in those universities. The research relied on the questionnaire as the primary tool for collecting data and information on the field side. Several statistical tests were adopted in terms of mean and standard deviations to diagnose the degree of agreement of the sample on the availability of indicators related to the research variables, as well as the correlation and regression analysis test to verify the correlation and influence. The research found a significant correlation between organizational flexibility and electronic human resources management practices. And the existence of a significant impact related to the dimensions of organizational flexibility in the practices of electronic human resources management. Based on the conclusions of the research, a set of proposals was developed, the most important of which was the need for university leaders in the surveyed universities to pay attention to verify the dimensions of organizational flexibility in organizational units, which can positively affect organizational performance based on electronic human resources management practices.